TREM-2 Receptor Expression Increases with 25(OH)D Vitamin Serum Levels in Patients with Pulmonary Sarcoidosis - Maria Bucova; Magda Suchankova; Elena Tibenska; Eva Tedlova; Juraj Demian; Ivan Majer; Helena Novosadova; Miroslav Tedla (Mediators of Inflammation)
TREM-1 and TREM-2 molecules are members of the TREM transmembrane glycoproteins. In our previous study we identified increased expressions of TREM-1 and TREM-2 receptors in pulmonary sarcoidosis (PS). Only a few studies concerning the association between vitamin D and TREM receptor expression can be found. The aim of our current study was to determine the association between the levels of an inactive form of 25(OH)D vitamin and TREM-1 and TREM-2 receptor expressions. We have detected low levels of 25(OH)D vitamin in 79% of PS patients. Only 21% of patients had normal serum level of 25(OH)D vitamin with values clustered within the low-normal range. The most striking findings were the increased TREM-2 expressions on myeloid cells surfaces in BALF of PS patients with normal 25(OH)D vitamin serum levels compared with those with its decreased levels. The total number of TREM-2 positive cells was 5.7 times higher and the percentage of TREM-2 positive cells was also significantly increased in BALF of PS patients with normal compared to PS patients with low 25(OH)D vitamin serum levels. A significant correlation between total TREM-2 expression and vitamin D levels has been detected too. However, we have not detected similar differences in TREM-1expression and 25(OH)D vitamin serum levels.